Studi Perencanaan Jetty Sebagai Bangunan Pelindung Muara Dalam Menyelesaikan Permasalahan Muara Sungai Air Hitam Bengkulu - M Gilang Indra Mardika; Julita Hayati; Reynaldi Kurniawan; Indri Rahmandhani Fitriana; Tera Melya Patrice Sihombing (Jurnal Infrastruktur, 2025)
One of the estuaries in Bengkulu Province, the Air Hitam River Estuary, has gradation and estuary drift problems based on Google Earth satellite observations annually. The cause is the occurrence of high sediment material and the phenomenon of longshore currents. The structural solution is the design of a jetty structure with a long type because the estuarine condition causes the need to remain open. This coastal protection aims to maintain estuary stability and regulate the stream flow. The methods used in the research methods are the Admiralty method in the processing of tidal data and the Hindcasting method from CERC in the processing of wind data. The results of the analysis provide a jetty length of 270 m with a width of 200 m between jetties. The left and right jetties have a peak width of 3 m and the highest building is 4 m from sea level with high tidal parameters of HHWL, MSL, and LLWL conditions are 78.21 m, 0.04 m, and -78.36 m, respectively. The breaking wave analysis derived a height of 2.50 m at a depth of -3.22 m which is utilized for infrastrcture dimension analysis. The coastal protection materials used with a 1:2 building slope on both jetties are tetrapods for the first and second layers, and boulders for the core layer. Used 0.5-2 tons weight of tetrapods for both sides of the jetty, 0.44-16.71 kg and 0.18-16.71 kg weight of boulder stones for both sides of the jetty, and toe protection used boulder stones weighing 43.69-157.28 kg and 18.39-157.28 kg for both sides of the jetty. Based on the literature study and estuary conditions, this design is capable of maintaining estuary stability and control river flow effectively.